1999
DOI: 10.1002/(sici)1521-3757(19990301)111:5<616::aid-ange616>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Valenzbindungsdiagramme – eine Hilfe zum Verständnis chemischer Reaktivität

Abstract: Eine einheitliche Beschreibung chemischer Reaktivität ermöglichen Valenzbindungsdiagramme, wie sie im Bild schematisch für einen einfachen Fall (nur Reaktant‐ und Produktzustände müssen betrachtet werden) und ein komplexeres System (ein Zwischenzustand spielt ebenfalls eine wichtige Rolle) gezeigt sind (RC = Reaktionskoordinate). Ihre Anwendung wird an Reaktivitäts‐ und mechanistischen Problemen der organischen und metallorganischen Chemie demonstriert: In‐situ‐DNA‐Reparatur, C‐F‐ und C‐H‐Aktivierung, SRN2c‐Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 199 publications
2
7
0
Order By: Relevance
“…The behavior of the displacement reaction for NH 3 + Cl 2 (Figure ) is an archetype that represents the set of B : ---(XY) systems, with the exception of quantitative aspects. The six VB structures which are depicted in Scheme can be converted to two-state curves, which intersect along the reaction coordinate, mix, avoid the crossing, and give rise to the TS and energy barrier for the displacement reaction of the XB . The so generated two-state diagram is called a VB state correlation diagram (VBSCD) , and is depicted Figure , which shows the numerical data for the target reaction while using the generic symbols, B : ---(XY) → (BX) + + : Y – , to emphasize the generality of the VB diagram.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of the displacement reaction for NH 3 + Cl 2 (Figure ) is an archetype that represents the set of B : ---(XY) systems, with the exception of quantitative aspects. The six VB structures which are depicted in Scheme can be converted to two-state curves, which intersect along the reaction coordinate, mix, avoid the crossing, and give rise to the TS and energy barrier for the displacement reaction of the XB . The so generated two-state diagram is called a VB state correlation diagram (VBSCD) , and is depicted Figure , which shows the numerical data for the target reaction while using the generic symbols, B : ---(XY) → (BX) + + : Y – , to emphasize the generality of the VB diagram.…”
Section: Discussionmentioning
confidence: 99%
“…The previous treatment of classical S N 2 nucleophilic displacements on alkyl halides, by one of us, has shown that this textbook process transpires due to the charge-transfer state that crosses the reactants state, X : – ---RX, and leads to the halide exchange. By analogy, we may envision that, in the process depicted in Chart , the XB complexes (B : ---XY) of bases/nucleophiles B : with dihalides or alkyl halides may undergo displacement reactions by a nucleophilic attack of B : on the halogen.…”
Section: Introductionmentioning
confidence: 99%
“…[52,85] Presently, we feel unable to evaluate the relative importance of the Hammond and the frontier-orbital effects, and for that reason consider it problematic to predict generally slopes of the correlation lines that imply changes in selectivities in the activation-controlled range. [86]…”
Section: Methodsmentioning
confidence: 99%
“…Further aspects of the oxidation mechanism and catalytic cycle were studied. Of initial interest was the mode of activation of the CÀH bond, which can occur by the formation of a donor ± acceptor complex, electron transfer, [11] or hydrogen abstraction. [12] The interaction of hydrocarbons with H 5 PV 2 Mo 10 O 40 was studied by measuring the appearance of the absorbance corresponding to the reduced POM at 750 nm.…”
mentioning
confidence: 99%